Redefining the Subsurface Biosphere: Characterization of Fungi Isolated From Energy-Limited Marine Deep Subsurface Sediment - Kiel Reese, Brandi; Sobol, Morgan S.; Bowles, Marshall Wayne; Hinrichs, Kai-Uwe (Frontiers in Fungal Biology, 2021)
The characterization of metabolically active fungal isolates within the deep marine subsurface will alter current ecosystem models and living biomass estimates that are limited to bacterial and archaeal populations. Although marine fungi have been studied for over fifty years, a detailed description of fungal populations within the deep subsurface is lacking. Fungi possess metabolic pathways capable of utilizing previously considered non-bioavailable energy reserves. Therefore, metabolically active fungi would occupy a unique niche within subsurface ecosystems, with the potential to provide an organic carbon source for heterotrophic prokaryotic populations from the transformation of non-bioavailable energy into substrates, as well as from the fungal necromass itself. These organic carbon sources are not currently being considered in subsurface energy budgets. Sediments from South Pacific Gyre subsurface, one of the most energy-limited environments on Earth, were collected during the Integrated Ocean Drilling Program Expedition 329. Anoxic and oxic sediment slurry enrichments using fresh sediment were used to isolate multiple fungal strains in media types that varied in organic carbon substrates and concentration. Metabolically active and dormant fungal populations were also determined from nucleic acids extracted from in situ cryopreserved South Pacific Gyre sediments. For further characterization of physical growth parameters, two isolates were chosen based on their representation of the whole South Pacific Gyre fungal community. Results from this study show that fungi have adapted to be metabolically active and key community members in South Pacific Gyre sediments and potentially within global biogeochemical cycles.